Studies on Cu2ZnSnS4 (CZTS) powder and thin film prepared from Molecular ink. (2021) - Ray, Jaymin; Patel, Kinjal; Patel, Keyur; Bhatt, Gopal; Parihar, Usha
Abstract: Copper Zinc Tin Sulphide (Cu2 ZnSnS4 ) is one of the most promising materials in the field of thin film based solar cell. Nanoparticles and ink form of CZTS prepared by chemical method is well-studied. In the present work CZTS powder made from chemical method and used to prepared films by physical evaporation technique, i.e. flash evaporation. CZTS films were prepared at 200 °C substrate temperature and annealed at 300 °C and 450 °C in vacuum for one hour. The structural, morphological, optical and electrical properties of the as-deposited and annealed were studied. The XRD confirms the wurtzite structure of the CZTS films. Atomic force microscopy indicates that the surface morphology also improves with the annealing. The band gap value of the annealed films is 1.7 eV, implied that the formation of the CZTS material. An electrical measurement signifies the p-type conductivity of the films. As a sum-up, as-deposited films were amorphous, non-uniform and highly resistive, and after annealing all had improve.